Protestant Providentialism in the Commonwealth of the Nobles: A critical view on Sarmatism - Kriegseisen, Wojciech (Kwartalnik Historyczny, 2022)
This study is devoted to providentialism, an element characteristic of Sarmatism – a dominant ideology and culture in the early modern Commonwealth of the nobles. The attachment of special weight to providence’s care of the state and the nobility seems to have been characteristic also of Protestant circles in the sixteenth and early seventeenth century, and therefore the culture of the nobles’ Sarmatism should not be reduced to its late form, dominated as it was by Catholicism in the late seventeenth and eighteenth centuries.